The Impact of Digital Transformation In Activating Remote Monitoring (Field study in the General Secretariat of Lattakia Governorate) - محمد, رامي (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aimed mainly to demonstrate the impact of digital transformation in its dimensions (technological environment, electronic management, electronic human resources management, electronic organizational communication) on the remote oversight of the General Secretariat of Lattakia Governorate. The researcher relied on the descriptive analytical method to describe the study variables and analyze them based on the primary data collected by conducting a field study in the General Secretariat of Lattakia Governorate. Among the results of the study, the statistical descriptions of the sample members’ answers showed that the latest devices, equipment, advanced technology, and material facilities are not obtained by the General Secretariat of Lattakia Governorate, and the available technological capabilities are not characterized by the high efficiency necessary for electronic administration..